Estimating Regional Poverty Lines With Scarce Data: An Application to Brazilian Regions - Carlos Roberto Azzoni; Fernando Silveira; Alexandre Iwata; Antonio Ibarra; Bernardo Diniz; Guilherme Moreira (European Regional Science Association (ERSA), 2006)
The recent emphasis on fighting poverty in Brazil makes the determination of the size of the targeted population an important issue (What is the right poverty line? What is the real size of the poor population? How much money should be given to each poor family?). The application of poverty lines based on national income levels tends to produce important distortions at the regional level. Using data from a Household Expenditure Survey (HES) that covered some regions in Brazil, the paper develops and applies a methodology to define poverty lines for all regions and urban areas. These lines are based on nutritional requirements, thus avoiding the purchasing power parity problem, and take into account non-monetary income and in-kind consumption, aspects that are very important at the rural level. The HES results are matched with Census data, allowing for the estimation of rural and urban poverty lines for Brazilian regions.
Keywords: 330